“GIRAgua” Project: Synthesis of International Cooperation - Carrasco, Pablo (Latin American Journal of Trade Policy, 2019)
The current use of water, in addition to being governed by a law that does not adapt to the needs or context of water abundance in the country, such as the 1982 Water Code, generates additional pressure on the basins and aquifers that are used intensively or overexploited by the mining industry and agribusiness; this keeps them thinking about the availability of water using outdated conventional technological solutions, which are not in line with the real situation of water scarcity in Chile. Considering this situation, the objective of this article is to present the “GIRAgua” project as an international cooperation project agreed between the Chilean Ministry of Public Works and the Dutch Ministry of Infrastructure and Environment, through the so-called “Letter of Intentions”, signed in July 2016, as a way to promote the rational use of water and the concepts of Integrated Water Resources Management and Water Governance; key paradigms to face the current context of aquifer overload, intensive use of water and inspire the contribution of citizens in the design of public water policies.